Guidance and Counselling Service: A Path to Enhance Academic Achievement for Secondary Schools’ Students - Bhutto, Qamar Zaman; Zafar, Jam Muhammad; Ullah, Naeem (Annals of Human and Social Sciences, 2023)
This article focuses on the importance of guidance and counselling services for improving learning outcomes of students in the secondary schools of Larkana Division. Guidance and counselling service is supportive to students in aligning their strengths, enhancing their learning outcomes, nurturing their interests and values, and ultimately facilitating the realisation of their complete potential. In present era of information technology it has become difficult for a student to take right direction in educational perspective. The need of a counsellor is felt more than ever. By using a quantitative study approach a questionnaire was developed to collect data from 200 Male and Female secondary school students of Larkana Division, Sindh, Pakistan. The study showed the need of strengthening teacher-pupil interaction, considering student subject selection and feelings, and addressing concerns related to exam challenges and curricular relevance. The Ministry of Education must develop counselling centres in both public and private secondary schools, as well as the implementation of comprehensive counselling curricula.